Assessment of household-type brown rice milling machine using different variety of rice - Alonzo,Bangie B. (City of Batac : MMSU, 2021)
ABSTRACT ALONZO, RANGIE B. and QUETALIAS, JANELLA T. 2021. Assessment of a Household Type Brown Rice Milling Machine Using Different Variety of Rice Undergraduate Thesis, Mariano Marcos State University, City of Batac, Ilocos Norte, Adviser: Engr. Carlito V. Santiago The study was conducted to evaluate the Brown Rice Milling Machine as to its! milling capacity, milling recovery, hulling efficiency, input capacity, output capacity, head rice recovery, broken rice recovery, and brewers rice recovery In terms of milling capacity, the Rc222 has the highest capacity with 8.67 kg/hr in single pass and in double pass, the capacity was 5.23 kg/hr. And it is highly significant The NSIC Rc222 was highly significant in terms of input capacity in both single pass and double pass with 21.86 kg/hr and 22.87 kg/hr, respectively. In output capacity, the PIONEER 79 was highly significant with a capacity of 6.70 kg/hr in single pass, and 7.06 kg/hr in double pass. In terms of brewer's rice recovery, the NSIC Re160 was highly significant with a percentage of 1.41 in single pass and 2.36 in double pass. KEYWORDS: single pass, double pass, milling performance
Thesis (BS in Agricultural Engineering) -- Mariano Marcos State University -- College of Engineering, City of Batac, 2021.